The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.transci.2005.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Serological screening for Leishmania infantum in asymptomatic blood donors living in an endemic area (Sicily, Italy)

Abstract: The purpose of our study was to assess whether Leishmania infantum parasitemia occurs in asymptomatic Leishmania-seropositive subjects. Samples from 500 blood donors were tested using an enzyme-linked immunosorbent assay (ELISA). Anti-Leishmania antibodies were not found in any sample. Our Wndings suggest that the risk of L. infantum transmission by blood transfusion in Sicily is very low. 

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Anti-Leishmania antibodies were found in 11 (0.75%) cases, among which Leishmania DNA was detected in four [41]. A previous screening of asymptomatic blood donors from northwestern Sicily, Italy did not detect any positive sample of L. infantum antibodies by ELISA [42]. These data confirm that the risk of TTL seems to be variable in different endemic/non-endemic Sicilian areas [41].…”
Section: Asymptomatic Cases Of Leishmania Infection and Studies On Blsupporting
confidence: 61%
“…Anti-Leishmania antibodies were found in 11 (0.75%) cases, among which Leishmania DNA was detected in four [41]. A previous screening of asymptomatic blood donors from northwestern Sicily, Italy did not detect any positive sample of L. infantum antibodies by ELISA [42]. These data confirm that the risk of TTL seems to be variable in different endemic/non-endemic Sicilian areas [41].…”
Section: Asymptomatic Cases Of Leishmania Infection and Studies On Blsupporting
confidence: 61%
“…This is in accordance with the low incidence of reported cases of VL in Italy, which is one of European countries with a slight endemicity. Furthermore, recent studies carried out in our region showed a low prevalence of seropositivity for L. infantum in blood donors [17,18]. …”
Section: Discussionmentioning
confidence: 92%
“…Moreover, the above tests frequently give false-negative results in immunocompromised patients even in the presence of positive kDNA amplification (23), making their sensitivity unsatisfactory for detecting asymptomatic Leishmania infection, which is characterized by low or intermittent parasitemia. Consequently, it is not surprising that data from IFAT, DAT, or ELISA have shown low seroprevalence among healthy subjects living in Mediterranean areas of high endemicity (11,48) or even in Middle Eastern areas, where parasitemia, evidenced by DNA amplification, may be present in 16% of the healthy population (16) ( Table 2). On the other hand, the high sensitivity of qualitative techniques such as immunoblotting (24,32,39,41) makes them excellent epidemiological tools for detecting past contact with the parasite, as well as ideal candidates for diagnosing subclinical infections.…”
Section: Discussionmentioning
confidence: 99%